Analisis Gaya Hidup Dalam Pengambilan Keputusan Pembelian Produk Batik pada Pasar Grosir Setono Pekalongan - Muhammad Danial Rosif; Ari Pradhanawati; Hari Susanta Nugraha (Universitas Diponegoro, 2015)
The spread of batik fashion popularity in recent decades developed into a part of people's lifestyles. With the emergence of modern batik nowadays, batik became popular. Consumers generally favor a creative and innovative products. Consumer purchasing decisions cannot be separated from the beneficial lifestyle and have good quality. Pasar Grosir Setono Pekalongan as one of the largest batik center in Pekalongan trying to adjust the product to consumer’s lifestyle. Based on the results of interviews is known that there is unstable wholesaler product sales at Pasar Grosir Setono Pekalongan. This study was aimed to know the influence of activities, interests, and opinions (Lifestyle) on batik product purchasing decisions at Pasar Grosir Setono PekalonganThe sampling technique used is Non-Probability Sampling and the sampling type used is Purposive Sampling. Sample in this research is 100 respondents consisting of Pasar Grosir Setono Pekalongan consumers. Data analysis using analysis qualitative and quantitative with validity and reliability, simple regression analysis, double regression analysis, t test and f test with program spss 16.0 for windows.From the research that has been done, it is known that the R2 value of 0.389 which means that the contribution of independent variables that influence the lifestyle of the dependent variable is the purchasing decision amounted to 38.9%, while the remaining 61.1% is influenced by variables outside lifestyle variables.Advice can be given in this study, the batik in Pasar Grosir Setono Pekalongan should pay attention to lifestyle factors, especially the consumer’s opinion because it has the highest influence over activity and interest aspects. Strategy that can be adopted for the manager and the wholesaler, they are should focus more on efforts to influence consumer opinion about the advantages as characteristics of Pasar Grosir Setono Pekalongan, giving affordable price to match for consumers because Pasar Grosir Setono Pekalongan is mostly focused product for wholesale selling being so affordable.